Понятие социального потенциала в интерпретации проблемы гендерного неравенства (по материалам социологических исследований) - Стрельник, Е. (Социология: теория, методы, маркетинг, 2006)
The author makes an attempt to conceptualize theoretically the notion of social potential and apply it to research of gender inequality and social potential of women in Ukrainian society nowadays. In this connection the gender inequality is defined as a difference in statuses of men and women in various spheres of society that is caused by influence of gender factor on the opportunities for determination and realization of their social potential. At the same time two constituents of social potential at objectiveand subjective levels are distinguished, such as: the availability of social resources(material, educational, professional, and cultural) as well as readiness to make use of them and realize the value of these resources, ways of their reproduction and increase. Also the author mentions empirical characteristics at a subjective level of social potential, in accordance with which subjective aspects of social potential women in present day Ukrainian society can be analyzed.